Effects of Adenosine Monophosphate Used in Combination with L‐Arginine on Female Rabbit Corpus Cavernosum Tissue. Issue 1 (1st April 2014) - Stücker, Olivier; Pons, Catherine; Neuzillet, Yann; Laemmel, Elisabeth; Lebret, Thierry
Abstract: Introduction: Sexual dysfunction is significantly more prevalent in women than in men. However, to date, no satisfactory oral treatment is yet available. Aim: The aim of this study was to study the effects of adenosine monophosphate (AMP) alone or its combination with L‐Arginine on the relaxation of the female rabbit corpus cavernosum. Methods: Cylinder strips from the corporal body of the excised clitoris from female New Zealand White rabbits were incubated in Krebs solution. Phenylephrine (PE) precontraction was achieved, then the drugs AMP and L‐Arginine were administered either independently or in sequential combinations to the strips under precontracted conditions. Main Outcome Measures: Contraction percentages were compared. Results: When precontraction was induced by PE 8 μM or 20 μM, AMP was shown to induce relaxation up to 25% in a dose‐dependent manner. The relaxation induced by L‐Arginine reached 15.6% at 5.10 −4 M vs. 16.5% at AMP 5.10 −4 M under the same experimental conditions. Nitric oxide (NO) synthase inhibitor N‐nitro‐L‐arginine strongly inhibited the relaxing effect provoked by AMP, suggesting that the action mechanism of this nucleotide is related to the NO pathway. The combination of L‐Arginine at 5.10 −4 M with AMP at different doses ranging from 5.10 −4 M to 10 −3 M significantly amplified the relaxing response up to 40.7% and 58%, respectively. Conclusions: Our results demonstrate that AMP induces a relaxing effect on the female rabbit corpora. They also show that L‐Arginine and AMP can potentiate each other and that a synergistic effect can be obtained by their combined use. Because only slight differences exist between both sexes in response to NO donors and/or nucleotide purines or in their use together, it is very likely that close biochemical mechanisms, although not to the same degree and not quite similar, are involved in the engorgement of the penis and the clitoris of New Zealand White rabbits.